Structural transformation of teff markets - Minten, Bart; Stifel, David; Tamru, Seneshaw (International Food Policy Research Institute, 2018)
Since the beginning of the 2000s, important changes have occurred in Ethiopia’s economy.1 In this chapter, the extent to which these changes have affected teff markets are assessed using primary data collected from wholesale markets and secondary data on teff prices and margins, obtained from Ethiopia’s Central Statistical Agency (CSA) and the Ethiopian Grain Trade Enterprise (EGTE). Five possible reasons are considered for teff market transformation and for the changes in teff price margins over the period 2001–2011.2 This study period has been influenced by changes in five factors that may have affected how teff markets function. First, fast economic and income growth is changing food demand. Second, urbanization is leading to larger rural–urban food and teff marketing flows. Third, investments in road infrastructure and a better organized transport sector have led to significant declines in real transportation costs. Fourth, the widespread availability of mobile phones has improved access to price information for a large number of players in the commercial food circuit and has led, for some, to a different way of sealing commercial deals. Fifth, increased adoption of modern inputs and better access to extension agents are likely to have contributed to an increase in teff supply.